Criteria-Based Validity Assessment in Legal Cases of Claimed Reduced Work Capacity - Klett, N.; Dohrenbusch, R.; Fischer, A.; Geiger, T.; Keller, F.; Kornhuber, Johannes; Littke, O.; Schütz, A.; Siegmann, Eva-Maria; Käfferlein, W.; Grömer, T.; Capito, E. S. (Psychological Injury and Law, 2026)
Medical Expert Witness Assessments (MEWA) are international standard to generate information involving medical questions in litigations, such as the capacity to work. While this procedure is widely utilized and guidelines for assessing the validity of symptoms using psychometric tools and non-psychometric criteria have been developed, the scientific foundation of this multimodal Criteria-Based Validity Assessment (CVA) is weak. This study aims to provide empirical validation of CVA using psychometric Symptom (SVT) and Performance Validity Tests (PVT) as areference point. 466 MEWA conducted in the law of the German Statutory Pension Insurance (GPI), all uniformly having addressed the question of the capacity to work, were analyzed. Information about scores regarding the Structured Inventory of Malingered Symptomatology (SIMS), Amsterdam Short-Term Memory Test (ASTM) aswell as the seven CVA criteria were extracted. A logistic regression using CVA data to group the MEWA into plausible and implausible (over- and/or under reporting of symptoms) cases showed a significant association between implausible cases and SIMS scores (OR= 1. 067; 95%- CI [1.037, 1.098]; p<. 0 01) as well as ASTM scores (OR= 0.965; 95%- CI [0.936, 0.994]; p<.05). In this highly comparable real-world dataset, we find evidence that CVA is indeed a valid tool in terms of convergent validity using a SVT and PVT as the point of reference and provide descriptive data on SVT and PVT that facilitates the interpretation of psychometric test results in such cases.
CRIS-Team Scopus Importer:2026-02-06
Keywords: Criteria-Based validity assessment; Medical expert witness assessment; Pension insurance; Performance validity test; Symptom validity test; Validation